Optimal design for a multi-level energy exploitation unit based on hydrogen storage combining methane reactor and carbon capture, utilization and storage. (June 2023) - Zheng, J.H.; Guo, J.C.; Li, Zhigang; Wu, Q.H.; Zhou, X.X.
Abstract: Development of the large-scale energy storage and application of the CCUS are the key strategies for the reduction of carbon emissions and energy consumption. This paper develops a multi-level energy exploitation unit (MEEU) based on hydrogen storage (HS) embedding with methane reactor (MR) and carbon capture, utilization and storage (CCUS), in order to make full use of energy sources and reduce the total investment cost and carbon emission. The proposed MEEU adopts a reasonable multi-energy coupling model of electricity, heating, hydrogen and methane based on seasonal HS coordinating with multi-operation state MR and CCUS. Furthermore, the optimal design problem for the MEEU is established to figure out the optimal system capacity configuration and corresponding operation strategy. Finally, the related case studies are conducted to compare the proposed MEEU, conventional energy storage unit (CESU) and normal hydrogen storage unit (NHSU) in terms of investment, operation cost, carbon emission cost and the efficiency of energy use. Moreover, the influences of the variation of on-grid electricity price and gas price on the optimal allocation of the MEEU are also investigated. The results indicated that the total cost of MEEU reduces 7.34% compared with the CESU and 1.68% compared with the NHSU. The energy consumption of MEEU reduces 4.5% compared with CESU and 2.17% compared with NHSU. The performance of the MEEU is superior under the condition of high gas prices. Highlights: Proposing a novel concept of multi-level energy exploitation unit. Optimizing allocation and operation strategy on economic and environmental benefits. Reducing 7.34% of the total cost compared with conventional energy storage unit. Contributing to the reduction of energy consumption and carbon emissions. The performance of the unit is superior under the condition of high gas price.